Эколого-физнологическис особенности популяции непарного шелкопряда (Porthetria dispar L.) в Нижнем Приднепровье. Сообщение III. Влияние корма на качественный состав тела куколок - Колыбин, В.А.; Зелинская, Л.М. (Вестник зоологии, 1971)
The qualitative composition of fodder plants and P. dispar L. pupae is analyzed which is of paramount importance for elucidating the population state and probable direction of its change in the future. The main fodder plants of P. dispar L. (oak, willow, false acacia, birch and alder) are highly various in qualitative composition of the leaf depending on the time of vegetation and growing conditions. The false acacia under conditions of the Lower Dnieper area is quile suitable lor normal growth and development of the pest. The content of reserve substances such as glycogen, carbohydrates, lipids and proteins is different in P. dispar L. pupae from different micropopulations. Their composition depenefs not only on the quality of the fodder but also on the life conditions of the caterpillars and later on determines the viability and fecundity of imago.